2021
DOI: 10.2196/25781
|View full text |Cite
|
Sign up to set email alerts
|

A Technological-Based Platform for Risk Assessment, Detection, and Prevention of Falls Among Home-Dwelling Older Adults: Protocol for a Quasi-Experimental Study

Abstract: Background According to the United Nations, it is estimated that by 2050, the number of people aged 80 years and older will have increased by 3 times. Increased longevity is often accompanied by structural and functional changes that occur throughout an individual’s lifespan. These changes are often aggravated by chronic comorbidities, adopted behaviors or lifestyles, and environmental exposure, among other factors. Some of the related outcomes are loss of muscle strength, decreased balance control… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The exercise intensity is divided into four levels of ABCD, and the intensity increases gradually; The exercise frequency shall be no <3 times a week. In terms of training monitoring, physiotherapists understand the training status of older adult and adjust the content through telephone interviews and home visits ( 11 , 18 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…The exercise intensity is divided into four levels of ABCD, and the intensity increases gradually; The exercise frequency shall be no <3 times a week. In terms of training monitoring, physiotherapists understand the training status of older adult and adjust the content through telephone interviews and home visits ( 11 , 18 , 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the moment, the database includes data from the years 2019-2022. If the number of measures is wanted to be increased, modern pervasive computing technology with sensors could provide new additions enabling continuous monitoring of selected health functions in home-dwelling older adults [ 16 , 17 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high score indicated a good balance ( 27 ). Several authors have reported that the test has excellent test-retest ( r = 0.97) and inter-evaluator reliabilities (kappa = 0.92) ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Besides fall history and physical function, factors including gender, age, medication history, comorbidity, etc., may also contribute to FOF in the elderly ( 15 , 16 ). The falls efficacy scale or a single question “Are you afraid of falling?” is a generally accepted tool used by researchers to measure FOF ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%